Neurocognitive profile of adolescents with early-onset schizophrenia and their unaffected siblings. (21st October 2022) - Vyas, Nora S.; Burke, Lisa; Netherwood, Siobhan; Caviston, Paul; Simic, Mima; Buchsbaum, Monte S.
Abstract: Background: We investigated the neurocognitive profiles of Early-Onset Schizophrenia (EOS; onset before age 18) and paired unaffected siblings and the little-studied effect of age-of-onset and duration of illness on cognitive performance. Methods: 31 EOS probands, and 31 of their siblings, had four cognitive domains assessed: (a) Memory: California Verbal Learning Test, and the Wechsler Memory Scale-Revised; (b) Working memory: Digit Span; (c) Attention: Degraded-Stimulus Continuous Performance Test, Span of Apprehension (SPAN), and Trail Making Test (TMT) part A; (d) Executive function: Wisconsin card sorting task, and TMT part B. Diagnosis was confirmed using the structured clinical interview for DSM-IV. Results: While EOS showed a generalised neurocognitive deficit (0.25–0.50 effect size) compared with siblings, across all cognitive domains, significantly greater patient deficits were observed with, working memory, attention, and executive function and minimal differences for digit span forward, block design and false alarms on the SPAN-12 confirmed by repeated measures MANOVA. Patients with earlier onset (12–15) showed greater deficits on false alarm and digits backward scores. Siblings showed individual cognitive task profiles similar to patients, confirming familial effects. EOS showed much more variable scores than siblings with more individual tasks showing 2 SD deficits than siblings. Long duration patients had greater z-score variability across tasks. Conclusions: Duration of illness was a more important characteristic in patients with onset 16 and over than in younger onset patients with comparable durations. Both the similarity of sibling pair profiles and greater patient variability across task provide further support for neurobiological heterogeneity in schizophrenia.